A comparative analysis of environmental literacy skills among Adiwiyata school students: A study at SMA 8 and SMA 12 Banjarmasin - Aristin, Nevy Farista; Hastuti, Karunia Puji; Andini, Andini; Arisanty, Deasy; Angriani, Parida; Arini, Dini Noor (Jurnal Teori dan Praksis Pembelajaran IPS, 2026)
This research aims to analyze the environmental literacy skills possessed by students from SMA 8 Banjarmasin and SMA 12 Banjarmasin, both designated as Adiwiyata schools at the provincial level of Kalimantan Selatan. This study employs the quantitative approach, particularly the comparative method. The study population consisted of 476 students in the XI grade, where 185 students were from SMA 12 Banjarmasin and 133 students from SMA 8 Banjarmasin. The research employed a combination of cognitive and skills tests, and a set of questionnaires to measure students’ attitudes and behaviors toward the environment. The Mann-Whitney test was used to analyze the data, and the necessary tests included tests of homogeneity and normality. Based on the study’s results, there is no significant difference in the environmental literacy skills of Adiwiyata school students at the provincial level. The similarity in the level of environmental literacy for students of SMA 8 and SMA 12 Banjarmasin illustrates the impacts of provincial policy standards and the Adiwiyata program. These research insights could highlight some areas for growth concerning students’ awareness and capabilities. On the other hand, they could also support the development of environmental education in integration or interdisciplinary approaches to formal education.